New trends and technological challenges in the industrial production and purification of fructo-oligosaccharides - Nobre, Clarisse (2015)
An increased commercial interest in fructo-oligosaccharides (FOS) has emerged in the last decade due to their prebiotic activity. At large scale, the FOS are produced by microbial enzymes from sucrose. A mixture of FOS and other saccharides is obtained in this process. The presence of such saccharides reduces the prebiotic, caloric and cariogenic value of the final product. Therefore, many efforts have been conducted to obtain a product with increased FOS purity. This review comprises the most important technological and physicochemical aspects including FOS production and recovery processes; safety, dose and health claims concerning its intake; and commercially available FOS.